Japan MG registry: Chronological surveys over 10 years. Issue 1 (13th October 2022) - Suzuki, Shigeaki; Masuda, Masayuki; Uzawa, Akiyuki; Nagane, Yuriko; Konno, Shingo; Suzuki, Yasushi; Kubota, Tomoya; Sugimoto, Takamichi; Samukawa, Makoto; Watanabe, Genya; Ishizuchi, Kei; Akamine, Hiroyuki; et al.
Abstract: The primary purpose of the Japanese myasthenia gravis registry (JAMG‐R) has been to research and promote high‐quality medical care for MG patients in Japan. We reviewed the findings of surveys performed by JAMG‐R over an ~10‐y period. The first goal for favorable quality of life (QOL) is a status of minimal manifestations (MM) or better with an oral prednisolone (PSL) dose of 5 mg/d or less (MM‐5 mg). E arly and aggressive use of nonoral f ast‐acting t reatment together with low‐dose oral PSL (the "EFT strategy") is recommended to reduce disease severity with minimal oral steroid use so that the MM‐5 mg target can be met as soon as possible. We conducted the fourth largest multicenter survey ever in 2021, obtaining detailed clinical information from 1710 consecutive MG patients all over Japan, and compared the 2021 surveys with those from 2012 and 2015. The frequency of patients treated with EFT strategies showed a gradual increase, reaching 39% of the total MG patients in the 2021 survey. The current and maximum dose of PSL and the number of days at high‐dose (>20 mg/d) PSL showed decreases. Survey results indicate that as EFT strategies have spread, the percentage of patients on MM‐5 mg has increased. We again confirmed that MM‐5 mg was associated with favorable QOL in the 2021 survey. Recent data regarding COVID‐19 suggests that it did not seriously impact the MG population in Japan; unfortunately, refractory MG, observed in 21% of patients, is still an unresolved problem.